2020
DOI: 10.52106/2766-3213.1006
|View full text |Cite
|
Sign up to set email alerts
|

Managing Bipolar Disorder in Time of COVID-19 Pandemic

Abstract: People with bipolar disorder are at high risk of serious complications during the COVID-19 pandemic. Limited access to care, lifestyle, health condition and other clinical characteristics increase the risk of contracting the new coronavirus disease, with more risk of developing severe forms, as well as that of bipolar relapse. Here, we will describe some problematic situations that may be encountered by bipolar patients during this pandemic period, and the measures that can be taken to reduce the impact of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Previous research was able to show that social distancing has a negative impact on psychological well-being in the general population [45,46], and specifically in individuals with BD, not least because of subsequent changes in routines, employment, and social support [28,29]. Specifically, social support is very important when it comes to avoiding recurrence of BD and striving for remission [47,48]; thus, it is obvious that withdrawal of social contacts leads to more emotional distress in BD [49]. Further, earlier research found that COVID-19-induced lockdowns and consequent social distancing result in a higher risk of depressive relapses [17] and more symptoms of somatization [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research was able to show that social distancing has a negative impact on psychological well-being in the general population [45,46], and specifically in individuals with BD, not least because of subsequent changes in routines, employment, and social support [28,29]. Specifically, social support is very important when it comes to avoiding recurrence of BD and striving for remission [47,48]; thus, it is obvious that withdrawal of social contacts leads to more emotional distress in BD [49]. Further, earlier research found that COVID-19-induced lockdowns and consequent social distancing result in a higher risk of depressive relapses [17] and more symptoms of somatization [28].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of benzodiazepines and hypnotics ought to be conditioned by the nonattendance of the hazard of respiratory trouble and liver disappointment for which these atoms contraindicate. In common, the concomitant utilization of psychotropic sedate and other drugs that will be utilized within the administration of patients with COVID-19 infers closer observing of diverse physiological capacities, in specific heart, liver, kidney, respiratory function, and blood counts 17 .…”
Section: Bipolar Disorder Therapy During Post-covid/long Covidmentioning
confidence: 99%
“…미국의 보건복지부 및 보훈부에서는 국가 차원에서 군인들의 정신 건강을 위해 다양한 어플리케이션을 개발했는데, 그중 외상 및 스 트레스 장애와 직접적으로 관련된 어플리케이션이 다수를 차지한 다 (Owen et al, 2018). 'PTSD Coach'는 자조 관리를 위한 어플리케 이션으로, PTSD에 대한 교육과 함께 스트레스 평가 및 관리를 위 한 콘텐츠로 구성되어 사용자들에게 높은 만족도 평가를 받았고, RCT 연구로도 그 효과성이 입증되었다 (Kuhn et al, 2014;Kuhn et al, 2017;Miner et al, 2016) (Karrouri, Hammani, & Otheman, 2020;Stefana et al, 2020).…”
Section: Ptsd 관련 어플리케이션unclassified